Numerical modeling of the physical parameters of the heated-water dissociation interface into the natural gas hydrates reservoir. (5th August 2016) - Li, Mingchuan; Fan, Shuanshi; Su, Yuliang; Lu, Mingjing
Graphical abstract: The variation laws of physical parameters into hydrate reservoir during the heated-water dissociation. Highlights: Mass transfer models were built considering the hydrate bulk as one flow. Numerical solutions were presented with the difference method. Iterative calculation processes were provided after linearization. The variation laws of the physical parameters were obtained. Abstract: In this study, one flow field was considered for the hydrate bulk, and one-dimensional mass transfer mathematical models, which were included three phases, were built for the heated-water dissociation interface of a natural gas hydrate in porous media, with the aid of the Darcy seepage principle. Numerical solutions for these models were presented, by using the numerical difference method and the linearization method, in conjunction with an iterative scheme. An example model application was presented to carry on researching the sensitive parameters into the hydrate reservoir; and the variation laws were fitted for permeability, saturation and pressure during the dissociation process in the hydrate reservoir. The hydrate permeability was reduced to the hydrate zone value of 12.5 × 10 −9  m 2 with increasing distance; however, with increasing time, the hydrate permeability increased to that of porous media (55 × 10 −9  m 2 ). The hydrate saturation increased to the initial value of 45% with increasing distance, but gradually decreased over time. The water saturation decreased to that of irreducible water (17%) with increasing distance, but increased over time. The hydrate pressure increased with increasing distance, but was slightly lower than the initial value of 3.0 MPa for the boundary effect. The hydrate pressure decreased with increasing time, with a reduction from 24.14% to 21.82%.